Modelling and Predicting of the Characteristics of a Photovoltaic Generator on a Horizontal and Tilted Surface - Mustapha Elyaqouti; Lahoussine Bouhouch; Ahmed Ihlal (Institute of Advanced Engineering and Science, 2016)
In the present paper, we will attempt to predict the Ipv-Vpv output characteristic of a photovoltaic generator (PVG) and consequently the generated electric power. This will be possible through modeling, extracting the electrical parameters of the PVG under study and also, by estimating the global incident solar radiation, on a surface, first horizontally, and then tilted to a given angle. Mathematical models developed in Matlab, to characterize the studied PVG are validated by experimental data of the PVG manufacture. While models associated with global radiation are validated by measurements taken by the meteorological station installed on the laboratory site ERTAIER (Team for Research in Technology and Advanced Engineering of Renewable Energies) of Higher School of Technology Agadir (ESTA).